Original articleCerebral childhood and adolescent X-linked adrenoleukodystrophy. Clinical presentation, neurophysiological, neuroimaging and biochemical investigations - Zgorzalewicz-Stachowiak, Małgorzata; Stradomska, Teresa Joanna; Bartkowiak, Zuzanna; Galas-Zgorzalewicz, Bożena (Folia Neuropathologica, 2006)
Clinical, neurophysiological, neuroimaging and biochemical studies were performed in five boys with childhood and adolescent form of cerebral X-ALD, which is a very rare disease in developmental age. In all patients, rapidly progressive spasticity, ataxia and mental deterioration were found. Seizures occurred in four of them. Additionally, visual and hearing impairment were observed in four and three patients respectively. Adrenal insufficiency was also diagnosed in four cases. MR revealed extensive demyelination located mainly symmetrically in the parieto-occipital areas, in one patient in whom asymmetrical lesions in that region were found. All patients had abnormal visual, brainstem and somatosensory evoked potentials recording, reflecting the central demyelination occurring in X-ALD. The clinical diagnosis in every case was confirmed by the significantly elevated concentration of very long chain fatty acids (VLCFA) measured in plasma in comparison to normal values